PENGARUH SKEPTISISME PROFESIONAL, PENGALAMAN AUDITOR, KOMPETENSI AUDITOR DAN BEBAN KERJA TERHADAP PENDETEKSIAN KECURANGAN - Muhammad Rafnes; Nora Hilmia Primasari (Jurnal Akuntansi dan Keuangan, 2020)
This study aims to determine the effect of professional skepticism, auditor experience, auditor competence and workload on fraud detection. The population in this study were KAPs in the Central Jakarta area. The sampling technique used was simple random sampling technique. The analysis tool used is multiple linear regression. The results showed that professional skepticism and auditor competence had no effect on fraud detection, while auditor experience and workload had a positive effect on fraud detection.